Expectancy Damages for Breach of Contract: A Primer and Critique - David H. Vernon (Washington University Law Quarterly, 1976)
This Article is devoted primarily to describing and analyzing the conceptual framework within which courts traditionally have awarded expectancy damages—the “primer” and “critique” of the title. Expectancy rules lie at the center of traditional theory and are widely accepted. In many instances, however, they create problems in application and thus frequently are ignored by the courts. The existence of several different and contradictory bases for recovery in any given suit creates further problems.
Keywords: Contracts; Damages